Re)conceptualizing translation as a dynamic dialogue of constraints. - Rędzioch-Korkuz, Anna (Sign Systems Studies, 2025)
The intersection between translation studies and semiotics has been addressed in numerous publications and approaches to researching translation. However, at least within translation studies, this intersection has been visible mainly in cases in which non-linguistic signs come into play, whereas genuine semiotic frameworks have proven to be too broad or abstract. This has led to a conceptual and ontological paradox: on the one hand, translation scholars have been struggling to move beyond linguistics, but, on the other hand, most of them still place a strong emphasis on lingual translation. As a result, 'translation' is no longer a precise term broad enough to include contemporary types of this activity. This paper is a proposal made to reconceptualize translation as a dynamic process of dialogue between relevant constraints. Situated between translation semiotics and translation studies, the theoretical model described here underlines the role of constraints as well as the universal semiotic nature of translation.